On solving fuzzy delay differential equation using bezier curves - Ali F. Jameel; Sardar G. Amen; Azizan Saaban; Noraziah H. Man (International Journal of Electrical and Computer Engineering (IJECE), 2020)
In this article, we plan to use Bezier curves method to solve linear fuzzy delay differential equations. A Bezier curves method is presented and modified to solve fuzzy delay problems taking the advantages of the fuzzy set theory properties. The approximate solution with different degrees is compared to the exact solution to confirm that the linear fuzzy delay differential equations process is accurate and efficient. Numerical example is explained and analyzed involved first order linear fuzzy delay differential equations to demonstrate these proper features of this proposed problem.